Association between environmental tobacco smoke exposure and dementia syndromes. Issue 1 (26th October 2012) - Chen, Ruoling; Wilson, Kenneth; Chen, Yang; Zhang, Dongmei; Qin, Xia; He, Meizi; Hu, Zhi; Ma, Ying; Copeland, John R
Abstract : Objectives: Environmental tobacco smoke (ETS) has a range of adverse health effects, but its association with dementia remains unclear and with dementia syndromes unknown. We examined the dose–response relationship between ETS exposure and dementia syndromes. Methods: Using a standard method of GMS, we interviewed 5921 people aged ≥60 years in five provinces in China in 2007–2009 and characterised their ETS exposure. Five levels of dementia syndrome were diagnosed using the Automated Geriatric Examination for Computer Assisted Taxonomy instrument. The relative risk (RR) of moderate (levels 1–2) and severe (levels 3–5) dementia syndromes among participants exposed to ETS was calculated in multivariate adjusted regression models. Results: 626 participants (10.6%) had severe dementia syndromes and 869 (14.7%) moderate syndromes. Participants exposed to ETS had a significantly increased risk of severe syndromes (adjusted RR 1.29, 95% CI 1.05 to 1.59). This was dose-dependently related to exposure level and duration. The cumulative exposure dose data showed an adjusted RR of 0.99 (95% CI 0.76 to 1.28) for >0–24 level years of exposure, 1.15 (95% CI 0.93 to 1.42) for 25–49 level years, 1.18 (95% CI 0.87 to 1.59) for 59–74 level years, 1.39 (95% CI 1.03 to 1.84) for 75–99 level years and 1.95 (95% CI 1.34 to 2.83) for ≥100 level years. Significant associations with severe syndromes were found in never smokers and in former/current smokers. There were no positive associations between ETS and moderate dementia syndromes. Conclusions: ETS should be considered an important risk factor for severe dementia syndromes. Avoidance of ETS may reduce the rates of severe dementia syndromes worldwide.